Disrupted Balance of Angiogenic and Antiangiogenic Signalings in Preeclampsia. (9th February 2011) - Furuya, Mitsuko; Kurasawa, Kentaro; Nagahama, Kiyotaka; Kawachi, Kae; Nozawa, Akinori; Takahashi, Tsuneo; Aoki, Ichiro
Abstract : The placenta plays a central role in governing local circulatory system that mediates maternal condition and fetal growth. In early gestational phases, the placenta exerts properties of invasion and neovascularization for successful placentation. Extravillous invasive trophoblasts replace uterine endometrial vasculature and establish local blood pathway to obtain oxygen and nutrients from the mother. In later phases, the placenta promotes villous angiogenesis and vascular maturation that are finely controlled by angiogenic and antiangiogenic molecules. Among various molecules involved in placental neovascularization, vascular endothelial growth factor receptors (VEGFRs) and angiotensin II receptor type 1 (AT1) mediate important signaling pathways for maternal circulatory system and fetal growth. VEGFR1 and VEGFR2 are functional receptors for placental growth factor (PlGF) and VEGF, respectively, and PlGF-VEGFR1 and VEGF-VEGFR2 interactions are disturbed in many preeclamptic patients by excess amount of soluble form of VEGFR1 (also named sFlt1), a natural PlGF/VEGF antagonist. Recent studies have disclosed that excessive sFlt1 production in the placenta and aberrant AT1 signaling in the mother are closely associated with the pathology of preeclampsia and intrauterine growth restriction (IUGR). In this paper, neovascularization of the placenta and pathological events associated with disrupted balance between angiogenic and antiangiogenic signaling in preeclampsia are discussed.